Successful Repair and Management of Severe Scalp Avulsion Incurred during Birth in an Extremely Low Birth Weight Infant - Shoko Takahashi; Yu Kanai; Yayoi Miyazono; Daisuke Hitaka; Yuki Fujita; Yoichiro Shibuya; Hidetoshi Takada (Case Reports in Pediatrics)
Introduction. Minor head trauma, such as scalp abrasion, is relatively common during vaginal delivery, whereas fatal head trauma is rare. This case report describes the successful repair and management of severe scalp avulsion that occurred during vaginal delivery and consequent hemorrhagic shock in an extremely low birth weight infant. Case Presentation. An extremely low birth weight infant (26 weeks’ gestational age) sustained extensive scalp avulsion during vaginal delivery that exposed the skull. The scalp laceration began in the frontal temporal region and extended bilaterally along the temporal region for 20 cm. The infant experienced hemorrhagic shock soon after birth due to bleeding from the wound and was placed in a closed incubator for intensive care. At 7 h after birth, the wounds were repaired using sutures. Bleeding was quickly controlled, and the infant recovered from hemorrhagic shock. A wet dressing was applied to the wound, and the flap healed without necrosis. Conclusion. We successfully repaired severe scalp avulsion in this case. Scalp avulsion can cause severe bleeding and death. Bleeding control and the preservation of circulation are the most important factors in its repair and maintenance. In this case, suturing the wound effectively controlled the bleeding, and the application of wet dressing and a high-humidity environment thereafter may have contributed to the scalp’s engraftment.